Probable aerosol transmission of severe fever with thrombocytopenia syndrome virus in southeastern China. (December 2015) - Gong, Z.; Gu, S.; Zhang, Y.; Sun, J.; Wu, X.; Ling, F.; Shi, W.; Zhang, P.; Li, D.; Mao, H.; Zhang, L.; Wen, D.; et al.
Abstract: Some clusters of severe fever with thrombocytopenia syndrome virus (SFTSV) infection were reported in China as of 2010. However, to date, there has been no epidemiologic evidence of aerosol transmission of SFTSV. Epidemiologic investigations were conducted after a cluster of 13 cases of SFTSV in May 2014. A total of 13 cases, including 11 confirmed cases and one clinically diagnosed case, were identified besides the case of the index patient. The index patient experienced onset of SFTSV on 23 April and died on 1 May. The patients with secondary cases had onset from 10 to 16 May, peaking on 13 May. Moreover, eight secondary cases occurred in family members of the index patient, and the other five cases occurred in neighbors of the index patient. According to epidemiologic investigations, patients 1, 3, 4, 5, 6, 7, 9 and 12 contracted the disease through contact with blood of the index patient. Notably, patients 8 and 10 did not have a history of contact with the blood of the index patient, but they stayed in the mourning hall for hours. SFTSV could be transmitted from person to person by direct contact and/or aerosol transmission, and it is important to consider aerosol transmission as a possible transmission route.